Organizational Resilience in Emerging Markets: Insights from the Gamarra Commercial Hub, Peru - Hans Jhordan Silva Torralva (GECONTEC: Revista Internacional de Gestión del Conocimiento y la Tecnología)
This study examines the relationship between organizational resilience and sociodemographic factors in textile and garment microenterprises located in the Gamarra commercial emporium (Lima, Peru) during the COVID-19 health crisis. Based on a sample of 147 business managers, the research employed factor analysis, ANOVA tests, and both linear and logistic regression models. Findings suggest that organizational resilience operates as a multidimensional construct, structured around eight empirical factors that exhibit adequate internal consistency and discriminant validity. Additionally, variables such as gender, age, and duration of commercial engagement emerged as significant predictors of resilience levels. Specifically, age contributed positively, whereas longer tenure in Gamarra reduced resilience likelihood. Prediction models achieved over 85% accuracy in distinguishing between high- and low-resilience enterprises. The study concludes that strengthening adaptive capabilities, promoting distributed leadership, and reinforcing strategic planning represent essential strategies for enhancing resilience in uncertain environments.